ANALISIS KESANTUNAN BERBAHASA DALAM TINDAK TUTUR PEMBAWA ACARA SHABEKURI 007 - Muhammad Corel Sadewa; Dwi Astuti Retno Lestari; Komara Mulya (Universitas Negeri Jakarta, 2025)
This study aims to describe the politeness of the language used by the presenters in the Shabekuri 007 based on the theory proposed by Brown and Levinson (1987), Ide (1982), and Mizutani-Mizutani (1987). In speech, there is possibility of a face threatening act by each party that can interfere the communication process, so that there are rules that limit the actions of speakers and partners as well as strategies taken to establish good communication. The data collected with a free-to-talk method and analyzed by pragmatics equivalent method. The research results are described descriptively. The results of this study are that from 106 utterances, it was found that there were six markers of politeness in Mizutani-Mizutani’s (1987), namely intonations, particles at the end of sentences, sentences that seem doubtful, aizuchi, politely Japanese usage, and conveying the intention of the desire indirectly. Based on Ide’s rules of politeness (1982) there are 71 utterances that ignore these rules and 35 utterances that fulfill these rules. The rules consist of being polite to people with higher position, greater power, and to older people. Brown and Levinson's (1987) politeness strategies used consist of negative politeness strategies, on-record strategies, positive politeness strategies, and off-record strategies.